Africa's recent oil boom : are the same mistakes being made again? Investigating the effect of the recent surge in oil prices upon the prospects of long term development in Sub-Saharan Africa - Rhodes, Anton (Department of Political Studies, 2014)
Includes bibliographical references (leaves 101-107).